2016
DOI: 10.1590/s0100-204x2016000200003
|View full text |Cite
|
Sign up to set email alerts
|

Número mínimo de medições para a avaliação acurada de características agronômicas de pinhão-manso

Abstract: Resumo -O objetivo deste trabalho foi identificar o método mais eficaz para estimar coeficientes de repetibilidade em progênies de meios-irmãos de pinhão-manso (Jatropha curcas) e predizer o número mínimo de medições necessárias para algumas características agronômicas da oleaginosa. Avaliaram-se 18 famílias de meios-irmãos, em delineamento de blocos ao acaso, com três repetições, de 2009 a 2013. Nesse período, as seguintes características foram avaliadas: altura de plantas, diâmetro do caule, número de ramos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…The F-test also revealed a significant effect for measurements, which indicates that there has been a change in the mean of the genotypes over the years. These results are similar to those obtained for other perennial crops (Lopes et al, 2001;Degenhardt et al, 2002;Danner et al, 2010;Bruna et al, 2012;Negreiros et al, 2014;Lessa et al, 2014;Teodoro et al, 2016) and reinforce the need to study the minimum number of measurements to select superior Brazil nut genotypes for a productive increase. The Scott-Knott test clustered the 75 Brazil nut genotypes in three homogeneous groups for the number of fruits and two for the dry mass of seeds ( Table 2).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The F-test also revealed a significant effect for measurements, which indicates that there has been a change in the mean of the genotypes over the years. These results are similar to those obtained for other perennial crops (Lopes et al, 2001;Degenhardt et al, 2002;Danner et al, 2010;Bruna et al, 2012;Negreiros et al, 2014;Lessa et al, 2014;Teodoro et al, 2016) and reinforce the need to study the minimum number of measurements to select superior Brazil nut genotypes for a productive increase. The Scott-Knott test clustered the 75 Brazil nut genotypes in three homogeneous groups for the number of fruits and two for the dry mass of seeds ( Table 2).…”
Section: Methodssupporting
confidence: 85%
“…The dimensioning of the number of measurements has been conducted for several perennial crops such as acerola (Lopes et al, 2001), guava (Degenhardt et al, 2002), araçazeiro and pitangueira (Danner et al, 2010), peach (Bruna et al, 2012), sweet orange (Negreiros et al, 2014), banana , and Jatropha (Teodoro et al, 2016). The repeatability coefficient in the Brazil nut was estimated by Pedrozo et al (2015) and Assis (2016) from the methodology of mixed models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to install a genetic breeding program of Jatropha in Brazil numerous studies have been conducted in recent years, such as studies on genetic diversity (Rosado et al, 2010;Bhering et al, 2015), estimates of genetic parameters Teodoro et al, 2016d) and gains with selection Peixoto et al, 2016), repeatibility , Teodoro et al, 2016b, and path analysis (Teodoro et al, 2016c). However, for the formation of base populations for practicing the selection, diallel is the main genetic design used (Cruz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In an assessment of 18 half-sib progenies of jatropha (Jatropha curcas), a species of Euphorbiaceae that is also oleaginous, Teodoro et al (2016) proposed that four measurements would be required to ensure an accurate evaluation (minimum 80%) of the analyzed traits, including productivity. These authors also indicated PCcov as the most accurate method to estimate the repeatability coefficient.…”
Section: Discussionmentioning
confidence: 99%